Dermatomyositis complicated with asymmetric peripheral neuritis on exacerbation: A case report and literature review. Issue 4 (30th August 2016) - Irie, Takashi; Shigeto, Hiroshi; Koge, Junpei; Yamaguchi, Hiroo; Murai, Hiroyuki; Kira, Jun‐ichi
Abstract: We describe a 69‐year‐old woman with dermatomyositis who presented with asymmetric peripheral neuritis. The patient first developed dermatomyositis at 39 years‐of‐age; her symptoms improved several years later with oral prednisolone treatment. A year and a half before admission to our hospital, she developed a sensory disturbance in her feet that gradually expanded to both legs with left dominance. Six months later, bilateral leg muscle weakness and proximal muscle tenderness appeared. Neurological examination at admission revealed proximal muscle weakness and atrophy of all four limbs. Ankle jerk was absent bilaterally. There was sensory impairment in the left hand and both lower limbs, with more severe involvement of the left side and the medial side. Electrophysiological tests showed decreased sensory nerve action potentials in the left superficial fibular nerve and bilateral sural nerves, and decreased motor action potentials in the bilateral fibular nerves. We diagnosed mononeuritis multiplex as a complication of dermatomyositis. Her symptoms of mononeuritis multiplex and dermatomyositis were successfully treated with intravenous methylprednisolone pulse therapy followed by oral prednisolone therapy. Although our literature search found nine cases of dermatomyositis with polyneuropathy/polyradiculoneuropathy, most of which involved axonal neuropathy, this is the first case report of dermatomyositis presenting with mononeuritis multiplex. Abstract : We report a 69‐year‐old woman with dermatomyositis who presented with asymmetric peripheral neuritis. Although our literature search revealed nine cases of dermatomyositis with polyneuropathy/polyradiculoneuropathy, most of which involved axonal neuropathy, this is the first case report of dermatomyositis presenting with mononeuritis multiplex. Our patient had recurrent episodes of dermatomyositis and mononeuritis multiplex, which were resolved by repeated intravenous methylprednisolone pulse, suggesting that repeated intravenous methylprednisolone pulse should be considered for such relapsing cases.